New Images of Maria Clementina Sobieska Stuart in Rome - Ceci, Francesca (Sensus Historiae, 2026)
This study presents a group of previously unpublished representations of the Polish noblewoman and Queen of Great Britain, Maria Clementina Sobieska. Together with her consort, James III Stuart, she spent her brief life in Rome, where significant material testifying to her presence is still preserved. Among these are her funerary monument in St Peter’s Basilica, depictions of her elaborate funeral ceremonies, as well as official prints and paintings portraying her in her royal capacity. In the 2025 exhibition held at the Capitoline Museums, dedicated to the presence of the Sobieski family in the Eternal City, the section on Maria Clementina featured two paintings depicting her in devout guise, together with her remarkable plaster bust painted to resemble bronze - thus far a unique example. Considered collectively, these three works enrich and nuance the image of a young woman who, despite the adversities she faced and the public role she was compelled to assume, consistently remained true to herself.